Description of Adolescents Self Control - Amalina Fildzah Fujilestari; Nur Oktavia Hidayati; Efri Widianti (LPPM STIKES KENDAL, 2020)
Adolescence is a transition and period of change when the norm is being violated, adolescents will be detained in LPKA. Therefore, in order not to cause any problems in LPKA, they need a good Self-control. Self-control is the ability to inhibit or prevent any behavior in a positive way by making appropriate decisions. This study aimed to determine the overview of self-control in adolescents at Class II Bandung Youth Correctional Facility (LPKA). Research method used was quantitative descriptive. The technique used was total sampling with a sample of 79 adolescents. The instrument used was Self-Control made by Tantri Maulida using Averill theory. The validity value was 0.60 and the realibility value was 0.673. Analysis of the data used descriptive analysis with frequency distribution. The result of this study showed that most respondents at LPKA Class II Bandung with a number of 41 respondents (51,9%) had moderate Self-control, 27 respondents (34,2%) had high Self- control, 9 respondents (11,4%) had very high Self-control, and 2 respondents (2,5%) had low Self-control. The conclusion of this study was that most respondents had moderate Self- control. Therefore, this research suggests that LPKA needs to provide more intensive guidance or education such as holding classes or program at LPKA, in order to improve self- control.